Artificial selection for increased dispersal results in lower fitness. (24th November 2019) - Zwoinska, Martyna K.; Larva, Tuuli; Sekajova, Zuzana; Carlsson, Hanne; Meurling, Sara; Maklakov, Alexei A.
Abstract: Dispersal often covaries with other traits, and this covariation was shown to have a genetic basis. Here, we wanted to explore to what extent genetic constraints and correlational selection can explain patterns of covariation between dispersal and key life‐history traits—lifespan and reproduction. A prediction from the fitness‐associated dispersal hypothesis was that lower genetic quality is associated with higher dispersal propensity as driven by the benefits of genetic mixing. We wanted to contrast it with a prediction from a different model that individuals putting more emphasis on current rather than future reproduction disperse more, as they are expected to be more risk‐prone and exploratory. However, if dispersal has inherent costs, this will also result in a negative genetic correlation between higher rates of dispersal and some aspects of performance. To explore this issue, we used the dioecious nematode Caenorhabditis remanei and selected for increased and decreased dispersal propensity for 10 generations, followed by five generations of relaxed selection. Dispersal propensity responded to selection, and females from high‐dispersal lines dispersed more than females from low‐dispersal lines. Females selected for increased dispersal propensity produced fewer offspring and were more likely to die from matricide, which is associated with a low physiological condition in Caenorhabditis nematodes. There was no evidence for differences in age‐specific reproductive effort between high‐ and low‐dispersal females. Rather, reproductive output of high‐dispersal females was consistently reduced. We argue that our data provide support for the fitness‐associated dispersal hypothesis. Abstract : Artificial selection for increased dispersal propensity (HD) results in lower female reproductive performance and lower physiological condition in comparison to lines selected for decreased dispersal propensity (LD). Such negative association between dispersal and quality is in agreement with the fitnessassociated dispersal hypothesis according to which lower quality genotypes disperse more as driven by the benefits of genetic mixing.